RADIOCHEMICAL DETERMINATION OF NUCLEAR DATA - Qaim, S. M. (The Nucleus, 2020)
A vast knowledge of nuclear data is available and is grouped under three headings, namely, nuclear structure, nuclear decay and nuclear reaction data. Data measurements are done using a large number of techniques, including the radiochemical method, which has been extensively worked out at Juelich. This method is used for preparation of high-quality samples for irradiation, isolation of the desired radioactive product from the strong matrix activity, and preparation of thin suitable sources for accurate measurement of the radioactivity. The radiochemical method is especially suitable for fundamental studies on light complex particle emission reactions and formation of low-lying isomeric states. The neutron induced reaction cross section data are also of practical application in fusion reactor technology, particularly for calculations on tritium breeding, gas production in structural materials and activation of reactor components. The charged particle induced reaction cross section data, on the other hand, are of significance in developing new production routes of novel positron emitters and therapeutic radionuclides at a cyclotron. A brief overview of all those studies is given.